Transmisi Intergenerasi Trauma Perang di Keluarga Palestina : Analisis Sistematis pada Tiga Generasi (1948-2024) - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar (Jurnal Ventilator, 2025)
This study analyzes the intergenerational transmission of war trauma across three generations of Palestinian families through a systematic meta-analysis of 47 longitudinal studies (1948–2024), comprising 12,873 participants. The findings confirm a PTSD prevalence rate of 73.4% in the first generation (n=4,291), 61.2% in the second generation (n=4,582), and 48.7% in the third generation (n=4,000). Furthermore, hierarchical regression analysis reveals a significant correlation between the severity of first-generation trauma and its manifestation in subsequent generations (r=0.68, p<0.001). The most dominant intergenerational trauma symptoms include anxiety (89.3%), depression (82.1%), and attachment disorders (76.5%). Structural equation modelling identifies three primary mediators of trauma transmission: parenting patterns (?=0.59), family trauma narratives (?=0.47), and epigenetic factors (?=0.41). Consequently, this study extends the findings of Danieli et al. (2016) on intergenerational trauma mechanisms and contributes to Kellermann's (2013) theoretical model on protective factors in trauma resilience. Unlike previous research by Hassan (2019), which focused on two generations, these findings reveal an adaptive pattern in the third generation through the development of collective resilience (82.3%) and positive coping strategies (77.8%), offering a novel perspective on the potential for intergenerational trauma healing in the context of prolonged conflict.